Fluorescent Nitric Oxide Photodonors Based on BODIPY and Rhodamine Antennae. Issue 47 (4th July 2019) - Parisi, Cristina; Failla, Mariacristina; Fraix, Aurore; Rolando, Barbara; Gianquinto, Eleonora; Spyrakis, Francesca; Gazzano, Elena; Riganti, Chiara; Lazzarato, Loretta; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract: Two novel NO photodonors (NOPDs) based on BODIPY and Rhodamine antennae activatable with the highly biocompatible green light are reported. Both NOPDs exhibit considerable fluorescence emission and release NO with remarkable quantum efficiencies. The combination of the photoreleasing and emissive performance for both compounds is superior to those exhibited by other NOPDs based on similar light‐harvesting centres, making them very intriguing for image‐guided phototherapeutic applications. Preliminary biological data prove their easy visualization in cell environment due to the intense green and orange‐red fluorescence and their photodynamic action on cancer cells due to the NO photo‐liberated. Abstract : BODIPY and Rhodamine‐based NO photodonors activatable by the highly biocompatible green light exhibit superior combination of fluorescence emission and NO release performances making them very intriguing for image‐guided phototherapeutic applications.